Corporate social responsibility a strategy to promote and guarantee the protection of the fundamental right to a healthy and balanced environment - Andrade Tacca, César; De la Cruz Huanca, Oswaldo (Revista de Derecho Ambiental, 2022)
Corporate social responsibility (hereinafter, CSR) contributes to sustainable development. It ensures the presence of business activity with positive impacts on society and its environment. Its main feature is voluntary compliance because it is an ethical business practice. This paper, however, analyzes and postulates CSR as a mandatory mandate in the Constitutional State, like compliance with it is not a matter of good will or an ethical practice. This is because CSR is a tool and strategy capable of promoting care for the fundamental right to a healthy and balanced environment. If this is so, then compliance becomes imperative, because companies have a duty to respect, protect and conserve the environment. In addition, in the Constitutional State, public and private authorities are obliged to act in accordance with the rights and fulfillment of the Constitution. In this context, it is an obligation to comply with and implement strategies that promote rights, and CSR is an instrument that companies should implement to protect the environment and legitimize the development of their activities, especially extractive activities, which are often a source of conflict.